Análise e projeto de superfícies seletivas em frequência multibanda e/ou banda larga - Silva Segundo, Francisco Carlos Gurgel da (2014)
Frequency selective surfaces (Frequency Selective Surface - FSS) are often used in various applications in telecommunications. Some of these applications may require that these structures have response with multiple resonance bands. Other applications require that the FSS response have large frequency range, to meet the necessary requirements. FSS to design with these features there are numerous techniques cited in the scientific literature. Thus, the purpose of this paper is to examine some common techniques such as: Overlap of FSS; Elements combined; Elements Elements convolucionados and fractals. And designing multiband FSS and / or broadband selecting simple ways in terms of construction and occupy the smallest possible space, aiming at practical applications. Given these requirements, three projects FSS were performed: a technology applied to IEEE 802.11 a/b/g/n and two projects for application in UWB. In project development, commercial software Ansoft DesignerTM and experimental results were satisfactory was used